Computational Fluid Dynamic Analysis to determine Downforce of Motorcycle Winglet - Mohd Amir Shazwan, Hashim; Baveendra Kumar, Premakumar; Shaheerthana, Suresh; Muhammad Izzat Nor, Ma'arof; Girma, Tadesse Chala (INTI International University, 2020)
Competitive motorcycling is all about being fast. However, frontal lift (i.e. ‘wheelie’) has high tendency to occur at high speed of travelling. Frontal lift is when the front wheel is no longer in contact with the ground, thus, results in the loss of traction, stability and control over the motorcycle. These undesired effects could be minimized by increasing the downforce (anti-lift) at the frontal section of the motorcycle. This could be achieved by incorporating a winglet which eliminates the necessity for the integration of electronic intervention. The objective of this study was to determine the downforce generated by a newly developed motorcycle winglet via Computational Fluid Dynamics (CFD) analysis. The CAD model for the winglet was developed via Inventor software and CFD was performed via ANSYS workbench. The analysis was performed on five (5) planes of the winglet. The result however showed a number of inconsistent readings of dynamic pressure gradient and drag pressure for all five (5) planes. It was found that the maximum drag pressure of 194.9 Pa was found on the pressure contour for plane Number 3. This is of course a direct contradiction to the goal of the incorporation of the winglet onto the motorcycle. Conclusively, due to lower dynamic pressure at the top layer of the winglet, the downforce generated is not significant to counter the frontal lift. Hence, the design characteristic of this newly developed winglet is not desired. For future study, the design used in this study could be used as the benchmark for improvement.